Gender Equity and Equality from Islamic Perspective: Malaysian Context - Wan Fariza Alyati; Wan Zakaria (Universitas Islam Negeri Imam Bonjol Padang, 2017)
The question of women has always attracted audiences from various religions, societies or civilizations. As a complete way of life, Islam has given special attention and position to women who will never find it in any system of belief and civilization. This paper discusses gender equity and equality from Islamic perspective and specifically looks it within Malaysian context. It also traces the historical involvement of Muslim women in nation building since Malaysia achieved her independence in 1957. This is important to show that the government of Malaysia has given special attention to women, especially Muslim women to play significant role and contribute positively to the society and nation building. This is in accordance to the government focus on positioning the wasatiyyah approach in line with the role of the state in preserving Shariah according to the maqasid al-shariah. The protection of women rights is therefore under the responsibilities of the government.